CASH WAQF IN KELANTAN: PROSPECTS AND CHALLENGES - Siti Rohana Mohamad; Zunaidah Sulong (Journal of Islamic, Social, Economics and Development, 2022)
Cash waqf is an innovative instrument for Islamic Social Finance (ISF). It has the potential to handle social concerns by supporting Muslims economy, education, welfare, religious issues, agriculture and social wellbeing. Cash waqf was introduced in Kelantan in 2015 under MAIK as a contemporary waqf instruments that are beneficial to the Muslims in the state. It increases the prospect of curbing poverty and a more structured socio-economic development in Kelantan. The objective of this paper is to look into the potential of cash waqf in dealing with the abovementioned issues, considering its flexibility and ease of collection. Besides that, this paper also attempts to address issues and challenges faced by the state of Kelantan in implementing cash waqf. They include lack of comprehensive legislation, lack of transparency and accountable governance, and lack of regulatory or framework that ensures effective collection and distribution.